A positive electrode material and its preparation method and application

By using a silane coupling agent combined with a carbon material on the surface of the layered oxide positive electrode material, polydopamine and metal oxide are coated to form a core-shell structure, which solves the problem of material being sensitive to air and improves air stability and electrochemical properties, while reducing production costs.

CN117613229BActive Publication Date: 2025-02-07JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311593643.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-27
Publication Date
2025-02-07
Estimated Expiration
2043-11-27

AI Technical Summary

Technical Problem

Nickel-rich layered oxide positive electrode material is sensitive to moisture and CO2 in the air, resulting in reduced capacity of the material, increased pH, affected processing performance, and deterioration of battery magnification and cycling performance.

Method used

A silane coupling agent is used to combine with a carbon material and as a bonding agent, polydopamine and metal oxide are coated on the surface of the layered oxide positive electrode material to form a core-shell structure to improve the air stability of the material.

Benefits of technology

It effectively protects the material from air humidity, improves the air stability of the layered oxide positive electrode material, improves the rate performance and circulation performance of the material, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117613229B_ABST
    Figure CN117613229B_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode material and a preparation method and application thereof. The positive electrode material of the present invention is a core-shell structure, with a layered oxide positive electrode material as the core, and a polydopamine layer, a silane coupling agent / carbon material composite layer and a metal oxide layer sequentially coated on the layered oxide positive electrode material; the present invention uses the silane coupling agent composited with the carbon material as a linker to link and coat the polydopamine and the metal oxide on the surface of the sodium ion layered oxide positive electrode material to obtain Na x Ni i Fe j Mn k M m O 2 @PAN@D 2 The composite layer of the silane coupling agent / carbon material of the present invention plays a connecting role, can optimize the organic (polydopamine layer)-inorganic (metal oxide layer) double coating layer, effectively protect the material from the influence of humidity in the air, and improve the air stability of the layered oxide positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium ion battery layered metal oxides Na x TMO2 (TM = transition metal) materials have attracted extensive attention from researchers due to their rich composition diversity and tunable electrochemical properties. Layered metal oxides are an extremely important class of positive electrode materials for sodium-ion batteries, such as NaNi 0.33 Fe 0.33 Mn 0.34 O2 material, which has high reversible capacity, stable structure and very good development prospects.

[0003] However, nickel-rich layered oxide cathode materials are extremely sensitive to moisture and CO2 in the ambient air. When the material is exposed to air, residual sodium compounds (NaOH and Na2CO3) are easily formed on the surface, causing the sodium in the material to form residual alkali, which will lead to: (1) reduced material capacity; (2) increased material pH, affecting material processing performance; (3) high residual alkali materials will lead to high gas production in the battery after being made into a battery, which will in turn deteriorate the battery's rate and cycle performance. This will greatly increase the cost of material production, storage and use. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a positive electrode material and a preparation method and application thereof. The present invention uses a silane coupling agent compounded with a carbon material as a linker to link and coat polydopamine and a metal oxide on the surface of a sodium ion layered oxide positive electrode material to obtain Na x Ni i Fe j Mn k M m O2@PAN@D2Or. The composite layer of the silane coupling agent / carbon material of the present invention plays a connecting role, can optimize the organic (polydopamine layer)-inorganic (metal oxide layer) double coating layer, effectively protect the material from the influence of humidity in the air, and improve the air stability of the layered oxide positive electrode material.

[0005] The first object of the present invention is to provide a positive electrode material, wherein the positive electrode material is a core-shell structure, with a layered oxide positive electrode material as a core, and a polydopamine layer, a silane coupling agent / carbon material composite layer and a metal oxide layer sequentially coated on the layered oxide positive electrode material;

[0006] The molecular formula of the layered oxide positive electrode material is Na x Nii Fe j Mn k M m O2;

[0007] Wherein, M is one or more of Li, B, Mg, Al, K, Ca, Ti, Co, V, Cr, Cu, Zn, Zr, Nb and Sn; i, j, k, m are the molar ratios of the corresponding elements, and satisfy 0≤i≤0.4, 0≤j≤0.5, 0≤k≤0.6, 0≤m≤0.2, i+j+k+m=1,0.6 <x≤1;

[0008] The metal oxide is selected from one or more of Al2O3, MnO, ZrO2, TiO2, and ZnO.

[0009] In one embodiment of the present invention, at least one or more of the following conditions are met:

[0010] The thickness of the polydopamine layer is 5 to 15 nm;

[0011] The thickness of the metal oxide layer is 15-30 nm.

[0012] The second object of the present invention is to provide a method for preparing a positive electrode material, comprising the following steps:

[0013] Provide a layered oxide positive electrode material Na x Ni i Fe j Mn k M m O2; wherein M is one or more of Li, B, Mg, Al, K, Ca, Ti, Co, V, V, Cr, Cu, Zn, Zr, Nb and Sn; i, j, k, m are the molar ratios of the corresponding elements, and satisfy 0≤i≤0.4, 0≤j≤0.5, 0≤k≤0.6, 0≤m≤0.2, i+j+k+m=1,0.6 <x≤1;

[0014] Layered oxide cathode material Na x Ni i Fe j Mn k M m O2 is dispersed in an organic solvent, mixed evenly to obtain a suspension A, and a certain amount of dopamine hydrochloride is added to the suspension A, stirred and reacted to obtain a layered oxide positive electrode material with a polydopamine layer coated on the surface;

[0015] A certain amount of silane coupling agent and carbon material are mixed and dissolved in a solvent, and dispersed evenly to obtain a suspension B, and the obtained layered oxide positive electrode material coated with a polydopamine layer is mixed with the suspension B, and heated and stirred to react to obtain a positive electrode material with a composite layer of silane coupling agent / carbon material coated on the surface of the polydopamine layer;

[0016] The positive electrode material whose surface is coated with a silane coupling agent / carbon material composite layer and a certain amount of nano metal oxide are mixed and ball-milled to form a metal oxide layer on the silane coupling agent / carbon material composite layer to obtain the positive electrode material.

[0017] In one embodiment of the present invention, the layered oxide positive electrode material Na x Ni i Fe j Mn k M m O2 is prepared by the following method: Ni i Fe j Mn k M m The (OH)2 precursor is mixed with a sodium source by ball milling to obtain a mixed powder, and the mixed powder is heated, sintered, and ground to obtain the layered oxide positive electrode material Na x Ni i Fe j Mn k M m O2.

[0018] In one embodiment of the present invention, at least one or more of the following conditions are met:

[0019] The sodium source is one or more of sodium carbonate, sodium hydroxide, sodium acetate, sodium oxalate, and sodium nitrate;

[0020] The heating sintering temperature is 750-1100°C, the time is 6-20h, and the heating rate is 1-10°C / min;

[0021] The rotation speed of ball milling mixing is 300-800 r / min, and the ball milling time is 0.5-5 h.

[0022] In one embodiment of the present invention, at least one or more of the following conditions are met:

[0023] The organic solvent is selected from one or more of anhydrous ethanol, N-methyl-2-pyrrolidone and acetone;

[0024] The organic solvent and the layered oxide positive electrode material Na x Ni i Fe j Mn k M mThe mass ratio of O2 is 2 to 2.5:1;

[0025] The amount of dopamine hydrochloride added is the layered oxide positive electrode material Na x Ni i Fe j Mn k M m 0.5-1wt% of the mass of O2;

[0026] The pH value of the suspension A is 8 to 11;

[0027] The stirring reaction time is 5 to 15 hours, and the stirring speed is 200 to 550 rpm;

[0028] The method also includes drying the obtained layered oxide positive electrode material having the polydopamine layer coated on the surface thereof, wherein the drying temperature is 80 to 160° C. and the drying time is 3 to 8 hours;

[0029] The thickness of the polydopamine layer is 5 to 15 nm.

[0030] In one embodiment of the present invention, at least one or more of the following conditions are met:

[0031] The silane coupling agent is selected from one or more of allyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, heptadecafluorodecyltrimethoxysilane, tridecafluorooctyltriethoxysilane, trifluoropropylmethylcyclotrisiloxane, methyltrimethoxysilane, propyltrimethoxysilane, n-octyltriethoxysilane and decyltrimethoxysilane;

[0032] The silane coupling agent accounts for 1.5% of the layered oxide positive electrode material Na x Ni i Fe j Mn k M m 0.35wt% to 0.65wt% of O2 mass;

[0033] The conditions of the heating and stirring reaction are: the reaction temperature is 60-80°C, and the reaction time is 0.5-2.5h;

[0034] The carbon material is selected from one or more of conductive carbon black, graphite, carbon nanotubes, graphene, carbon nanofibers, and mesophase carbon microspheres;

[0035] The carbon material content accounts for 1.3% of the layered oxide positive electrode material Na x Ni i Fe j Mn k M m 0.2wt%~0.4wt% of O2 mass;

[0036] The reaction time of the heating and stirring reaction is 0.5-2.5h, and the heating temperature is 60-80°C;

[0037] The method also includes drying the positive electrode material of the composite layer of silane coupling agent / carbon material coated on the surface of the polydopamine layer, wherein the drying temperature is 80 to 120° C. and the drying time is 5 to 12 hours;

[0038] The solvent is selected from one or more of ethanol, methanol, propanol, toluene, acetone and benzene.

[0039] In one embodiment of the present invention, at least one or more of the following conditions are met:

[0040] The nano metal oxide is selected from one or more of Al2O3, MnO, ZrO2, TiO2, and ZnO;

[0041] The particle size of the nano metal oxide is 15 to 30 nm;

[0042] In the mixed ball milling, the ball milling speed is 500-900 r / min, and the ball milling time is 2-5 h;

[0043] The thickness of the metal oxide layer is 15-30 nm.

[0044] The third object of the present invention is to provide a positive electrode sheet, comprising the positive electrode material or the positive electrode material obtained by the preparation method.

[0045] A fourth object of the present invention is to provide a sodium ion battery comprising the positive electrode sheet.

[0046] The above technical solution of the present invention has the following advantages compared with the prior art:

[0047] 1. The polydopamine film formed by the polymerization of dopamine hydrochloride uniformly coats the layered oxide positive electrode material, which can effectively prevent the penetration of water molecules and carbon dioxide molecules in the air, avoid the problem of inducing the material to de-sodiumize itself or the oxidation of transition metals in the material to cause the material to de-sodiumize, and improve the air stability of the material. 2. The silane coupling agent composited with the carbon material is connected to the polydopamine layer to prepare for the connection of the metal oxide layer, wherein the composite carbon material can improve the electronic conductivity of the coating layer material and improve the rate performance of the material. 3. Through the connection effect of the silane coupling agent on the organic (polydopamine layer) and inorganic (metal oxide) materials, the oxide can be tightly coated on the surface of the material without sintering. Through this multi-layer coating, multiple protection of the material can be achieved, which can not only improve the structural stability of the material, inhibit the irreversible phase change of the material, prevent the material from directly contacting the electrolyte to produce side reactions that affect the battery performance, but also improve the cycle performance and rate performance of the material. 4. The multi-layer coating method provided by the present invention does not require secondary sintering and has lower energy consumption and production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0049] Figure 1 Schematic diagram of the layered oxide positive electrode material of the present invention.

[0050] Figure 2 1 is the XRD diagram of Example 1 of the present invention and Comparative Example 1.

[0051] Figure 3 It is a transmission electron microscope image of Example 1 of the present invention.

[0052] Explanation of the reference numerals in the specification: 1. layered oxide positive electrode material; 2. polydopamine layer; 3. composite layer of silane coupling agent / carbon material; 4. metal oxide layer. DETAILED DESCRIPTION

[0053] In order to solve the technical problems pointed out in the background technology, the present invention proposes a positive electrode material and a preparation method and application thereof.

[0054] The present invention adopts a silane coupling agent as a bridging agent, and covers the surface of the layered oxide positive electrode material with polydopamine and metal oxide, thereby improving the air stability of the material without losing the rate performance.

[0055] The present invention provides a positive electrode material, the positive electrode material comprising a silane coupling agent bridged double-coated layered oxide positive electrode material Na x Ni i Fe j Mnk M m O2@PAN@D2O r , which is a core-shell structure, with a layered oxide cathode material as the core, and a polydopamine layer, a composite layer of silane coupling agent / carbon material, and a metal oxide layer sequentially coated on the layered oxide cathode material;

[0056] The molecular formula of the layered oxide cathode material is Na x Ni i Fe j Mn k M m O2;

[0057] Among them, M is one or more of Li, B, Mg, Al, K, Ca, Ti, Co, V, Cr, Cu, Zn, Zr, Nb, and Sn; i, j, k, m are the molar ratios of the corresponding elements respectively, and satisfy 0≤i≤0.4, 0≤j≤0.5, 0≤k≤0.6, 0≤m≤0.2, i + j + k + m = 1, 0.6 < x ≤ 1; D is one or more of Mn, Zr, Ti, Zn, Zr, Al; r changes according to the valence state of the D element.

[0058] The metal oxide is selected from one or more of Al2O3, MnO, ZrO2, TiO2, ZnO.

[0059] In one embodiment of the present invention, at least one or more of the following conditions are satisfied:

[0060] The thickness of the polydopamine layer is 5 - 15 nm;

[0061] The thickness of the oxide layer is 15 - 30 nm;

[0062] The thickness of the composite layer of silane coupling agent / carbon material is 2 - 5 nm. This layer is a very thin layer, which mainly plays the role of bridging between the polydopamine layer and the metal oxide layer.

[0063] The present invention also provides a preparation method of a cathode material, including the following steps:

[0064] Provide a layered oxide cathode material Na x Ni i Fe j Mn k M m O2; Among them, M is Li + , B 3+ , Mg 2+ , Al 3+ , K + , Ca 2+ , Ti 4+, Co 3+ , V 3+ , V 4+ , Cr 3+ , Cu 2+ , Zn 2+ , Zr 4+ , Nb 5+ and Sn 4+ One or more of the following; i, j, k, m are the molar ratios of the corresponding elements respectively, and satisfy 0 < i ≤ 0.4, 0 < j ≤ 0.5, 0 < k ≤ 0.6, 0 < m ≤ 0.2, i + j + k + m = 1, 0.6 < x ≤ 1;

[0065] Disperse the layered oxide cathode material Na x Ni i Fe j Mn k M m O2 in an organic solvent, mix evenly to obtain suspension A, and add a certain amount of dopamine hydrochloride to suspension A, and stir to react to obtain a layered oxide cathode material with a polydopamine layer on the surface;

[0066] Mix a certain content of silane coupling agent and carbon material and dissolve them in a solvent, disperse evenly to obtain suspension B, mix the obtained layered oxide cathode material coated with a polydopamine layer with suspension B, heat and stir to react to obtain a cathode material with a composite layer of silane coupling agent / carbon material coated on the surface of the polydopamine layer;

[0067] Mix and ball-mill the cathode material with a composite layer of silane coupling agent / carbon material coated on the surface of the polydopamine layer and a certain amount of nano-metal oxide to form a metal oxide layer on the composite layer of silane coupling agent / carbon material to obtain the cathode material.

[0068] Furthermore, when 0.6 < x ≤ 0.8, the material is a P2-phase layered oxide; when 0.8 < x ≤ 1, the material is an O3-phase layered oxide.

[0069] In a specific embodiment, the layered oxide cathode material Na x Ni i Fe j Mn k M m O2 is prepared by the following method: Mix the Ni i Fe j Mn k M m (OH)2 precursor and a sodium source by ball-milling to obtain a mixed powder, heat and sinter the mixed powder, and grind to obtain the layered oxide cathode material Na x Ni i Fej Mn k M m O2.

[0070] In one embodiment of the present invention, at least one or more of the following conditions are met:

[0071] The sodium source is one or more of sodium carbonate, sodium hydroxide, sodium acetate, sodium oxalate, and sodium nitrate;

[0072] The heating sintering temperature is 750-1100°C, the time is 6-20h, and the heating rate is 1-10°C / min;

[0073] The rotation speed of ball milling mixing is 300-800 r / min, and the ball milling time is 0.5-5 h.

[0074] In a specific embodiment, at least one or more of the following conditions are met:

[0075] The organic solvent is selected from one or more of anhydrous ethanol, N-methyl-2-pyrrolidone and acetone;

[0076] The organic solvent and the layered oxide positive electrode material Na x Ni i Fe j Mn k M m The mass ratio of O2 is 2 to 2.5:1;

[0077] The amount of dopamine hydrochloride added is 0.5-1wt% of the mass of the layered oxide positive electrode material;

[0078] The pH value of the suspension A is 8 to 11;

[0079] The stirring reaction time is 5 to 15 hours, and the stirring speed is 200 to 550 rpm;

[0080] The method also includes drying the obtained layered oxide positive electrode material having the polydopamine layer coated on the surface thereof, wherein the drying temperature is 80 to 160° C. and the drying time is 3 to 8 hours;

[0081] The thickness of the polydopamine layer is 5 to 15 nm.

[0082] In a specific embodiment, at least one or more of the following conditions are met:

[0083] The silane coupling agent is selected from one or more of allyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, heptadecafluorodecyltrimethoxysilane, tridecafluorooctyltriethoxysilane, trifluoropropylmethylcyclotrisiloxane, methyltrimethoxysilane, propyltrimethoxysilane, n-octyltriethoxysilane and decyltrimethoxysilane;

[0084] In a specific embodiment, the present invention uses a silane coupling agent to tightly connect the polydopamine layer and the metal oxide layer, thereby avoiding the sintering process. In the prior art, ordinary oxide coatings require the chemical adhesion formed after sintering to tightly coat the material, while the present invention uses the cross-linking effect of the silane coupling agent to directly tightly connect the polydopamine layer and the metal oxide layer, directly omitting the sintering step; based on the poor electrical conductivity of the organic and inorganic substances selected by the present invention, the present invention composites the silane coupling agent with the carbon material, and connects the organic layer (polydopamine layer) and the inorganic layer (metal oxide layer) as an intermediate layer, which can improve the electrical conductivity of the designed material. If the carbon material is introduced into the outermost layer, the electrical conductivity within the layer cannot be guaranteed, so the carbon material is introduced between the polydopamine layer and the metal oxide layer, which can play a good conductive role and improve the electronic conductivity of the material.

[0085] The silane coupling agent accounts for 1.5% of the layered oxide positive electrode material Na x Ni i Fe j Mn k M m 0.35wt% to 0.65wt% of O2 mass;

[0086] The conditions of the heating and stirring reaction are: the reaction temperature is 60-80°C, and the reaction time is 0.5-2.5h;

[0087] The carbon material is selected from one or more of conductive carbon black, graphite, carbon nanotubes, graphene, carbon nanofibers, and mesophase carbon microspheres; preferably carbon nanotubes and carbon nanofibers.

[0088] Furthermore, the conductive carbon black is selected from acetylene black and Ketjen black.

[0089] The carbon material content accounts for 1.3% of the layered oxide positive electrode material Na x Ni i Fe j Mn k M m 0.2wt%~0.4wt% of O2 mass;

[0090] The reaction time of the heating and stirring reaction is 0.5-2.5h, and the heating temperature is 60-80°C;

[0091] The method also includes drying the positive electrode material of the composite layer of silane coupling agent / carbon material coated on the surface of the polydopamine layer, wherein the drying temperature is 80 to 120° C. and the drying time is 5 to 12 hours;

[0092] The solvent is selected from one or more of ethanol, methanol, propanol, toluene, acetone and benzene.

[0093] In a specific embodiment, at least one or more of the following conditions are met:

[0094] The metal oxide is selected from one or more of Al2O3, MnO, ZrO2, TiO2, and ZnO;

[0095] The particle size of the nano metal oxide is 15 to 30 nm;

[0096] In the mixed ball milling, the ball milling speed is 500-900 r / min, and the ball milling time is 2-5 h;

[0097] The thickness of the metal oxide layer is 15-30 nm.

[0098] During the preparation of the above positive electrode material, the reaction is carried out under the condition of humidity ≤ 5% to prevent the material from reacting with moisture in the air and affecting the performance.

[0099] The present invention provides a positive electrode sheet, comprising the positive electrode material or the positive electrode material obtained by the preparation method.

[0100] The present invention also provides a sodium ion battery, comprising the positive electrode sheet.

[0101] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0102] Example 1

[0103] This embodiment provides a method for preparing a layered oxide positive electrode material and its application.

[0104] (1) A method for preparing a layered oxide positive electrode material, the specific steps are as follows:

[0105] 1.1、Ni 0.28 Fe 33 Mn 0.34 Al 0.05 The (OH)2 precursor and the sodium source were placed in a ball mill and milled at a speed of 800 r / min for 1.5 h to fully mix them. The mixed powder was placed in a muffle furnace and solid-phase sintered at 900 °C for 15 h. After natural cooling and grinding, the layered oxide positive electrode material NaNi was obtained.0.28 Fe 33 Mn 0.34 Al 0.05 O2 is a black powder.

[0106] 1.2. The NaNi obtained in step 1.1 0.28 Fe 33 Mn 0.34 Al 0.05 The black powder of O2 is dispersed in anhydrous ethanol and dispersed at high speed for 20 minutes to obtain a uniform suspension A; when the pH value of suspension A is stabilized at 10, 0.8wt% dopamine hydrochloride is added to suspension A, which is placed on a magnetic stirrer and stirred for 8 hours to obtain suspension B; finally, suspension B is filtered, washed, and dried to obtain a polydopamine-coated layered oxide positive electrode material.

[0107] 1.3. Dissolve 0.5wt% of methyltrimethoxysilane and 0.25wt% of carbon nanofibers in an ethanol solution, disperse at high speed for a certain period of time to obtain a uniform suspension C, transfer the polydopamine-coated layered oxide positive electrode material obtained in step 1.2 to the suspension C, and place it on a heatable magnetic stirrer to heat and stir the reaction for 1 hour to obtain a uniformly mixed suspension D; filter, wash and dry the suspension D to obtain a silane coupling agent-bridged polydopamine-coated layered oxide positive electrode material.

[0108] 1.4. The silane coupling agent bridged polydopamine coated layered oxide positive electrode material obtained in step 1.3 and 0.35wt% of nano-alumina powder with a particle size of 15μm are placed in a ball mill and ball milled at a speed of 650r / min for 2.5h to allow the silane coupling agent to fully undergo a coupling reaction, tightly linking the polydopamine and the oxide together to obtain a silane coupling agent bridged double-coated PAN / Al2O3-NaNi 0.28 Fe 33 Mn 0.34 Al 0.05 O2 layered oxide positive electrode material; in the obtained positive electrode material, the polydopamine layer is 7nm and the metal oxide layer is 15nm.

[0109] (2) Application of layered oxide cathode materials - preparation of sodium ion batteries, as follows:

[0110] Preparation of sodium ion battery: Expose to 55% humidity for 3 days, then 0.28 Fe 33 Mn 0.34 Al 0.05The O2 material, the conductive agent SuperP, and the binder PVDF were ground evenly in a mass ratio of 8:1:1, and then an appropriate amount of NMP was added to make a slurry with a solid content of 68%, and evenly coated on the carbon-coated aluminum foil, dried at 80°C in a blast drying oven for 1h, and then dried at 120°C in a vacuum drying oven for 12h; then cut into 14mm round positive electrode sheets with a cutting machine. A sodium metal sheet with a diameter of 14mm and a thickness of 0.2mm was used as the negative electrode, a 0.1mol / L sodium perchlorate / ethylene carbonate / dimethyl carbonate solution was used as the electrolyte, and a WhatmanGF / F glass fiber with a diameter of 16mm was used as the diaphragm. The CR2032 button battery was assembled in a glove box filled with high-purity argon.

[0111] Battery performance test: The charge and discharge test was carried out at a current density of 0.1C using a constant current charge and discharge mode. The test items include: the first cycle charge and discharge of the material in the sodium ion battery, rate performance, and the capacity retention rate of 100 cycles of charge and discharge and 200 cycles of charge and discharge. Under the conditions of a discharge cut-off voltage of 2.0V and a charge cut-off voltage of 4.0V, the physical and chemical performance test results of the O3 phase layered oxide positive electrode material prepared in this embodiment are shown in Table 1.

[0112] Example 2

[0113] This embodiment is prepared completely according to the scheme of embodiment 1, and the difference from embodiment 1 is that 0.2wt% nano alumina powder is used for oxide coating.

[0114] Example 3

[0115] This embodiment is prepared completely according to the scheme of embodiment 1, and the difference from embodiment 1 is that 0.5wt% nano alumina powder is used for oxide coating.

[0116] Example 4

[0117] This embodiment is prepared completely according to the scheme of embodiment 1, and the difference from embodiment 1 is that the nano oxide used is nano titanium dioxide.

[0118] Comparative Example 1

[0119] This comparative example provides a preparation method and application of a layered oxide positive electrode material

[0120] This comparative example is similar to Example 1, except that:

[0121] (1) The preparation method of the layered oxide positive electrode material is as follows:

[0122] Ni 0.28 Fe 33 Mn 0.34 Al 0.05The (OH)2 precursor and the sodium source were placed in a ball mill and milled at a speed of 800 r / min for 1.5 h to fully mix them. The mixed powder was placed in a muffle furnace and solid-phase sintered at 900 °C for 15 h. After natural cooling and grinding, the layered oxide positive electrode material NaNi was obtained. 0.28 Fe 33 Mn 0.34 Al 0.05 O2 is a black powder.

[0123] (2) Application of layered oxide cathode materials - sodium ion battery

[0124] The sodium ion preparation and testing methods are the same as in Example 1.

[0125] Comparative Example 2

[0126] This comparative example provides a preparation method and application of a layered oxide positive electrode material

[0127] This comparative example is similar to Example 1, except that:

[0128] (1) The preparation method of the layered oxide positive electrode material is as follows:

[0129] 1.1. Ni 0.28 Fe 33 Mn 0.34 Al 0.05 The (OH)2 precursor and the sodium source were placed in a ball mill and milled at a speed of 800 r / min for 1.5 h to fully mix them. The mixed powder was placed in a muffle furnace and solid-phase sintered at 900 °C for 15 h. After natural cooling and grinding, the layered oxide positive electrode material NaNi was obtained. 0.28 Fe 33 Mn 0.34 Al 0.05 O2 is a black powder.

[0130] 1.2. The NaNi obtained in step A 0.28 Fe 33 Mn 0.34 Al 0.05 The black powder of O2 was dispersed in anhydrous ethanol and dispersed at high speed for 20 min to obtain a uniform suspension A. When the pH value of suspension A was stabilized at 10, 0.8 wt% dopamine hydrochloride was added to the suspension, which was placed on a magnetic stirrer and stirred for 8 h to obtain suspension B. Finally, suspension B was filtered, washed, and dried to obtain polydopamine-coated PAN-NaNi 0.28 Fe 33 Mn 0.34 Al 0.05 O2 layered oxide positive electrode material.

[0131] (2) Application of layered oxide cathode materials - sodium ion battery applications, as follows:

[0132] The sodium ion preparation and testing methods are the same as in Example 1.

[0133] Comparative Example 3

[0134] This comparative example provides a preparation method and application of a layered oxide positive electrode material

[0135] This comparative example is similar to Example 1, except that:

[0136] (1) The preparation method of the layered oxide positive electrode material is as follows:

[0137] 1.1. Ni 0.28 Fe 33 Mn 0.34 Al 0.05 The (OH)2 precursor and the sodium source were placed in a ball mill and milled at a speed of 800 r / min for 1.5 h to fully mix them. The mixed powder was placed in a muffle furnace and solid-phase sintered at high temperature for 15 h. After natural cooling and grinding, the layered oxide positive electrode material NaNi was obtained. 0.28 Fe 33 Mn 0.34 Al 0.05 O2 is a black powder.

[0138] 1.2. The NaNi obtained in step 1.1 0.28 Fe 33 Mn 0.34 Al 0.05 The black powder of O2 is dispersed in anhydrous ethanol and dispersed at high speed for 20 minutes to obtain a uniform suspension A; when the pH value of suspension A is stabilized at 10, 0.8wt% dopamine hydrochloride is added to suspension A, which is placed on a magnetic stirrer and stirred for 8 hours to obtain suspension B; finally, suspension B is filtered, washed, and dried to obtain a polydopamine-coated layered oxide positive electrode material.

[0139] 1.3. The polydopamine-coated layered oxide cathode material obtained in step 1.2 and 0.35 wt% of nano-alumina powder were placed in a ball mill, and ball milled at a speed of 650 r / min for 2.5 h to obtain a mixed layered oxide cathode material.

[0140] (2) Application of layered oxide cathode materials - preparation of sodium ion batteries, as follows:

[0141] The sodium ion preparation and testing methods are the same as in Example 1.

[0142] Table 1 Electrochemical performance of Examples 1 to 4 and Comparative Examples 1 to 3

[0143]

[0144] It can be seen from the experimental results in Table 1 that when the main material types of Examples 1 to 4 and Comparative Examples 1 to 3 are the same, the materials prepared by the silane coupling agent bridged double-coated layered oxide method provided by the present invention in Examples 1 to 4 have extremely excellent air stability. After being exposed to an environment with an air humidity of 55% for a period of time, the XRD of the material has not changed, indicating that the material prepared by this method has extremely excellent air stability in the air. In addition, the material prepared by this method has excellent rate performance and cycle stability. Comparative Example 1 has the same main material as Example 1, and does not adopt the surface coating method provided by the invention. After the positive electrode material of Comparative Example 1 was exposed to an environment with an air humidity of 55% for a period of time, the XRD diffraction peak shifted, and a new diffraction peak was generated, indicating that the air stability of the material without surface coating was poor. And the rate performance and cycle stability of the material in Comparative Example 1 are very different from those in Example 4. This shows that the Na prepared by the method provided by the present invention x Ni i Fe j Mn k M m O2@PAN@D2O r , which indeed improves the material's air stability, rate performance and cycle stability. Comparative Example 2 uses only dopamine for surface coating. Compared with Comparative Example 1, the rate performance and capacity retention rate of the material are improved, but compared with Example 1, the rate performance and capacity retention rate are limited, and new phases are formed when exposed to a certain humidity environment. Comparative Example 3 is similar to the method adopted in Example 1, except that no silane coupling agent is added. The capacity and rate performance of the material are relatively poor, indicating that the direct use of oxide mixing has a poor effect.

[0145] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material is a core-shell structure, with a layered oxide positive electrode material as a core, and a polydopamine layer, a silane coupling agent / carbon material composite layer and a metal oxide layer sequentially coated on the layered oxide positive electrode material; The molecular formula of the layered oxide positive electrode material is Na x Ni i Fe j Mn k M m O2; Wherein, M is one or more of Li, B, Mg, Al, K, Ca, Ti, Co, V, Cr, Cu, Zn, Zr, Nb and Sn; i, j, k, m are the molar ratios of the corresponding elements, and satisfy 0≤i≤0.4, 0≤j≤0.5, 0≤k≤0.6, 0≤m≤0.2, i+j+k+m=1,0.6 <x≤1。 2. The positive electrode material according to claim 1, characterized in that At least one or more of the following conditions must be met: The thickness of the polydopamine layer is 5 to 15 nm; The thickness of the metal oxide layer is 15 to 30 nm; The metal oxide is selected from one or more of Al2O3, MnO, ZrO2, TiO2, and ZnO.

3. A method for preparing a positive electrode material, characterized in that: The following steps are involved: Provide a layered oxide positive electrode material Na x Ni i Fe j Mn k M m O2; wherein M is one or more of Li, B, Mg, Al, K, Ca, Ti, Co, V, Cr, Cu, Zn, Zr, Nb and Sn; i, j, k, m are the molar ratios of the corresponding elements, and satisfy 0≤i≤0.4, 0≤j≤0.5, 0≤k≤0.6, 0≤m≤0.2, i+j+k+m=1,0.6 <x≤1; Layered oxide cathode material Na x Ni i Fe j Mn k M m O2 is dispersed in an organic solvent, mixed evenly to obtain a suspension A, and a certain amount of dopamine hydrochloride is added to the suspension A, stirred and reacted to obtain a layered oxide positive electrode material with a polydopamine layer coated on the surface; A certain amount of silane coupling agent and carbon material are mixed and dissolved in a solvent, and dispersed evenly to obtain a suspension B, and the obtained layered oxide positive electrode material coated with a polydopamine layer is mixed with the suspension B, and heated and stirred to react to obtain a positive electrode material with a composite layer of silane coupling agent / carbon material coated on the surface of the polydopamine layer; The positive electrode material whose surface is coated with a silane coupling agent / carbon material composite layer and a certain amount of nano metal oxide are mixed and ball-milled to form a metal oxide layer on the silane coupling agent / carbon material composite layer to obtain the positive electrode material.

4. The preparation method according to claim 3, characterized in that: The layered oxide positive electrode material Na x Ni i Fe j Mn k M m O2 is prepared by the following method: Ni i Fe j Mn k M m The (OH)2 precursor is mixed with a sodium source by ball milling to obtain a mixed powder, and the mixed powder is heated and sintered, and ground to obtain the layered oxide positive electrode material Na x Ni i Fe j Mn k M m O2.

5. The preparation method according to claim 4, characterized in that: At least one or more of the following conditions must be met: The sodium source is one or more of sodium carbonate, sodium hydroxide, sodium acetate, sodium oxalate, and sodium nitrate; The heating sintering temperature is 750-1100°C, the time is 6-20h, and the heating rate is 1-10°C / min; The rotation speed of ball milling mixing is 300-800 r / min, and the time is 0.5-5 h.

6. The preparation method according to claim 3, characterized in that: At least one or more of the following conditions must be met: The organic solvent is selected from one or more of anhydrous ethanol, N-methyl-2-pyrrolidone and acetone; The organic solvent and the layered oxide positive electrode material Na x Ni i Fe j Mn k M m The mass ratio of O2 is 2 to 2.5:1; The amount of dopamine hydrochloride added is the layered oxide positive electrode material Na x Ni i Fe j Mn k M m 0.5-1wt% of the mass of O2; The pH value of the suspension A is 8 to 11; The stirring reaction time is 5 to 15 hours, and the stirring speed is 200 to 550 rpm; The method also includes drying the obtained layered oxide positive electrode material having the polydopamine layer coated on the surface thereof, wherein the drying temperature is 80 to 160° C. and the drying time is 3 to 8 hours; The thickness of the polydopamine layer is 5 to 15 nm.

7. The preparation method according to claim 3, characterized in that: At least one or more of the following conditions must be met: The silane coupling agent is selected from one or more of allyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, heptadecafluorodecyltrimethoxysilane, tridecafluorooctyltriethoxysilane, trifluoropropylmethylcyclotrisiloxane, methyltrimethoxysilane, propyltrimethoxysilane, n-octyltriethoxysilane and decyltrimethoxysilane; The silane coupling agent accounts for 1.5% of the layered oxide positive electrode material Na x Ni i Fe j Mn k M m 0.35wt% to 0.65wt% of O2 mass; The temperature of the heating and stirring reaction is 60-80°C and the time is 0.5-2.5h; The carbon material is selected from one or more of conductive carbon black, graphite, carbon nanotubes, graphene, carbon nanofibers, and mesophase carbon microspheres; The carbon material content accounts for 1.3% of the layered oxide positive electrode material Na x Ni i Fe j Mn k M m 0.2wt%~0.4wt% of O2 mass; The reaction time of the heating and stirring reaction is 0.5-2.5h, and the heating temperature is 60-80°C; The method also includes drying the positive electrode material of the composite layer of silane coupling agent / carbon material coated on the surface of the polydopamine layer, wherein the drying temperature is 80 to 120° C. and the drying time is 5 to 12 hours.

8. The preparation method according to claim 3, characterized in that: At least one or more of the following conditions must be met: The nano metal oxide is selected from one or more of Al2O3, MnO, ZrO2, TiO2, and ZnO; The particle size of the nano metal oxide is 15 to 30 nm; In the mixed ball milling, the ball milling speed is 500-900 r / min, and the ball milling time is 2-5 h; The thickness of the metal oxide layer is 15-30 nm.

9. A positive electrode sheet, characterized in that: The invention comprises the positive electrode material according to claim 1 or 2, or the positive electrode material obtained by the preparation method according to any one of claims 3 to 8.

10. A sodium ion battery, characterized in that: Including the positive electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation method of polydopamine-coated sodium ion battery positive electrode material

    CN114204028A

  • High-rate sodium ion battery positive electrode material and preparation method thereof

    CN115020709A